Study of psychological aspects of the safety culture of motorcyclists' behaviors in Indonesia's urban road traffic: Construction of road users' belief systems - Andrijanto; Makoto Itoh; Sunardy; Michael Jonathan (IATSS Research, 2025)
The poor development of traffic safety culture by road traffic organizations in Indonesia has caused motorcyclists to behave irresponsibly while driving. Consequently, some behaviors may cause conflict with other road users, which may affect traffic safety. Therefore, studying the beliefs of road users regarding motorcyclists' behavior can describe the psychological aspects of the safety culture in urban road traffic. In this study, we used the reciprocal safety culture model as a framework, by applying a behavioral-based safety program to investigate motorcyclists' critical behaviors in urban areas in Indonesia. Adapting Ward's transformation model of belief systems to a behavior, we approach the psychological aspects of the traffic safety culture by observing the relationship between motorcyclists' critical behaviors and belief systems. We explore the belief system of Ward's model using a driving safety questionnaire (DSQ) and a cause-effect questionnaire. By applying multiple linear regression to the DSQ results, we revealed six motorcyclist behaviors critical to safety that affect car drivers and pedestrians. Furthermore, we constructed the belief systems of these behaviors by investigating behavioral beliefs, attitudes, normative beliefs, perceived norms, perceived control, and control beliefs to reveal “what road users think” about motorcyclits' behaviors related to traffic safety culture in the urban area.